Strategic Flexibility and Employee Creativity: A Moderating Role of Leader’s Education - Alshammari, Waleed Mansi; Ali, Dhakir Abbas (Journal of Economics and Behavioral Studies, 2024)
This study aims to explore the relationship between strategic flexibility and employee creativity in the context of Hail Health Cluster Saudi Arabia. This study has used two dimensions of strategic flexibility such as coordination flexibility and resource flexibility. Furthermore, this study also aims to investigate the role of a leader’s education as a moderator. For the data analysis, this study has collected data from 184 participants consisting of nurses, medical staff, and non-medical staff over three months July to August 2024. Further, on the data SEM-PLS technique is used to test the validity and decision-making about the hypothesis. The finding suggests that both coordination flexibility and resource flexibility significantly relate to employee creativity in healthcare clusters. Moreover, the education of the leader plays a moderating role among the variables. These findings are based on the Hail health cluster and offer valuable insights not only for the healthcare sector but for production sectors as well.